Mobilizing Cathedral Metaphors: The Case of 'Sacred Space, Common Ground'. Issue 4 (1st October 2016) - Muskett, Judith A.
Abstract : A range of metaphors has been mobilized to enliven the discourse of cathedral scholarship. Such imaginative terms can also stimulate theory and empirical investigation around the function of iconic cathedral buildings. Against the background of the emerging field of Cathedral Studies, this article reflects on a relatively new metaphor: 'sacred space, common ground'. The study takes inspiration from the adventures of Lewis Carroll's Alice; and the reflection on the metaphor is conducted through the lens of the 'Looking-glass room'. It is shown that the new metaphor highlights rich opportunities for mission yet also inherent tensions in two faces of cathedral life. The article concludes by offering suggestions for future empirical research within Cathedral Studies.